How February 2022 redefines extreme floods in Australia - Julien Lerat; Jai Vaze (Communications Earth & Environment)
Abstract In February 2022, eastern Australia experienced an extreme flood due to a combination of intense rainfall and close to saturation initial soil water conditions. It resulted in record-breaking water levels and flood volumes, leading to Australia’s largest total insurance claim for a single flood event. Here we analyse the physical factors underlying this event and compare them with a large dataset of floods in Australia dating back to 1950. Our findings show that February 2022 had the largest impact on design flood volumes with a 1% annual exceedance probability, which are expected to increase by 16% on average across the affected region. Additionally, this flood prompted major changes in national flood risk management, including upgrades to flood warning networks and a comprehensive review of the flood insurance sector.